AB1184 BONE MINERAL DENSITY, TRABECULAR BONE SCORE AND 3D-DXA ASSESSMENT IN ADULT PATIENTSWITH A POSITIVE AND NEGATIVE GENETICAL TESTING FOR HYPOPHOSPHATASIA. (June 2019) - Tornero, Carolina; Coronado, Monica; Humbert, Ludovic; García-Carazo, Sara; Lancha, Carmen; Monachello, Domenico; Dominguez-Gadea, Luis; Balsa, Alejandro; Aguado, Pilar
Abstract : Background: Scarce evidence exists on the assessment of bone mineral density (BMD ) in adult Hypophosphatasia (HPP). Recent studies suggest that dual-energy X-ray absorptiometry (DXA) could not appropriately predict their fracture risk and note the importance on further explore bone microstructure. Objectives: To evaluate BMD at the lumbar spine (LS) and proximal femur (PF) assessed by DXA, the trabecular bone score (TBS) at the LS and the fracture risk assessment (FRAX and adjusted by TBS, T-FRAX) in patients with persistent low alkaline phosphatase levels (ALP) and HPP genetically confirmed (HPP TG +) compared with a group of subjects with the same biochemical abnormality and a negative HPP genetic test (HPP TG-). As a secondary objective, to assess the cortical and trabecular bone at the PF using DXA-based 3D modeling. Methods: Seventy-three subjects with persistent low ALP levels - at least two values < 35 IU/L and none > 45 IU/L - and a genetic test for HPP performed were included. Individuals were distributed into 2 groups according to their genetic status. BMD was measured using GE-LUNAR iDXA and TBS. The 3D-SHAPER software was employed in a subgroup of 52 subjects matched by age, gender and body mass index. A clinical questionnaire and a battery of lab measures to assess risk factors for Osteoporosis were also performed. Results: Demographic, densitometric, TBS and 3D-DXA parameters are shown in table 1 . Of the 73 subjects included, 38 (52%) had pathogenic mutations in ALPL. Between postmenopausal women and men above 50 years, 9 subjects (29%) with ALPL mutations had osteopenia and 4 (13%), osteoporosis whereas 4 (13%) and 2 (6, 5%) were detected in the HPP-GT group, respectively (p>0, 05). Between premenopausal women and men under age 50, only 2 (5%) showed low BMD (Z-score < -2). BMD at femoral neck was significantly lower in the HPP + GT group compared to the HPP- GT group (0.864 ± 0.18 vs 0.948 ± 0.16 (p=0.014), similar findings were found for Wards area (0.695 ± 0.14 and 0.781 ± 0.16, p=0.021) and a trend was observed at the femoral diaphysis (p=0, 076). BMD at the LS and TBS assessment did not show differences. Major, hip FRAX and T-FRAX were superior in the HPP + GT group. In terms of the parameters of bone metabolism, ALP levels were lower in the HPP + GT (p= 0.0004), serum phosphate levels were higher in this group (p=0.01) and the rest did not show differences. The 3D-SHAPER software was applied in a subgroup of 52 subjects: volumetric BMD at the PF was lower in the HPP + GT (873, 6 ± 84, 4 g/cm 3 vs 819, 4 ± 95, 3 g/cm 3 ; p = 0.035) with no differences in trabecular vBMD (p=0.117). Conclusion: HPP + GT group showed less BMD at femoral neck and wards area and this trend was also observed at the diaphysis. At the femur, vBMD was also lower in this group. No differences in BMD at the lumbar spine and in TBS were found. These findings and its value for predicting the risk of fractures, specially in atypical femoral fractures, must be elucidated. Disclosure of Interests: Carolina Tornero: None declared, Monica Coronado: None declared, Ludovic Humbert: None declared, Sara García-Carazo: None declared, Carmen Lancha: None declared, Domenico Monachello: None declared, Luis Dominguez-Gadea: None declared, Alejandro Balsa Grant/research support from: Abbvie, Pfizer, Novartis, BMS, Nordic, Sanofi, Consultant for: Abbvie, Pfizer, Novartis, BMS, Nordic, Sanofi, Sandoz, Lilly, Paid instructor for: Pfizer, Speakers bureau: Pfizer, Novartis, UCB, Nordic, Sanofi, Sandoz, Lilly, Pilar Aguado: None declared